Mitochondrial DNA mutations accumulated in HIV-1-infected children who have an excellent virological response when exposed to long-term antiretroviral therapy. (25th July 2018) - Ouyang, Yabo; Wei, Feili; Qiao, Luxin; Liu, Kai; Dong, Yaowu; Guo, Xianghua; Wang, Shanshan; Pang, Lijun; Lin, Minghua; Zhang, Fujie; Lin, Dongdong; Chen, Dexi
Abstract: Objectives: There is growing concern about mitochondrial DNA (mtDNA) mutations with long-term NRTI exposure in HIV-1 infected children. Methods: Twenty-four HIV-1 infected children who started ART more than 2 years earlier who had an excellent virological response and had not changed their regimen were enrolled retrospectively. Their corresponding PBMCs in 2009 (T1), 2010 (T2) and 2013 (T3) were included. Sequencing of the entire mtDNA using next-generation sequencing revealed the spectrum of mtDNA variants. Results: The trend showed that the number of mtDNA mutations during ART occurred as T1 < T2 < T3 ( P = 0.086). Interestingly, the numbers of whole mtDNA mutations at T3 (median 41, range 24–62) were significantly greater than at T1 (34, 25–46, P = 0.029). A positive correlation was found between total mtDNA mutations and treatment time ( r = 0.352, P = 0.002). During the observation period, mtDNA mutations more frequently occurred in the D-loop, cytochrome b (CYTB) and 12S rRNA regions. The heteroplasmic ratio of T3 was higher than that of T1 in CYTB and 12S rRNA ( P = 0.034 and P = 0.042, respectively). High heteroplasmic population levels were found at nt 263 (A263G, D-loop) and nt 8860 (A8860G, ATPase6). A significant difference in heteroplasmy between T1, T2 and T3 occurred at nt 14783 (T14783C, CYTB, P = 0.048, T3 > T2 > T1). Conclusions: Our findings reveal the spectrum of mtDNA variants in HIV-1-infected children who had an excellent virological response. mtDNA mutations accumulated during ART may play an important role in facilitating the occurrence of mitochondrial dysfunction.